2020
DOI: 10.1007/s42399-020-00660-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Early Initiation of Breastfeeding Among Mothers in Dhaka City, Bangladesh: a Cross-sectional Study

Abstract: Early initiation of breastfeeding (EIBF) is crucial for mothers as well as children's health, and also has the potential to prevent neonatal mortality. Thus, this study aimed to assess the prevalence and factors associated with EIBF among mothers in Dhaka City, Bangladesh. A cross-sectional study was conducted from January to July 2019, based on a sample of 422 mothers of children aged under 6 months. Data were collected by in-person interviews from a hospital's outdoor through a structured questionnaire consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Similar to the observations of previous studies [35,41,[57][58][59][60][61], this study found that infants whose mothers practiced SSC were more likely to receive TIBF. A linkage could be drawn to the success in breastfeeding outcomes as a result of the provision of sensory experiences of touch and thermal regulation, which trigger the release of oxytocin for breastmilk production [28,35].…”
Section: Plos Onesupporting
confidence: 90%
“…Similar to the observations of previous studies [35,41,[57][58][59][60][61], this study found that infants whose mothers practiced SSC were more likely to receive TIBF. A linkage could be drawn to the success in breastfeeding outcomes as a result of the provision of sensory experiences of touch and thermal regulation, which trigger the release of oxytocin for breastmilk production [28,35].…”
Section: Plos Onesupporting
confidence: 90%
“…27 Skin-to-skin contact between mothers and their newborns immediately after delivery facilitates the EIBF within the first hour of delivery. [29][30][31][32][33][34][35]…”
Section: Discussionmentioning
confidence: 99%
“…In line with this recommendation, the Ethiopian Ministry of Health Sector Development Programme Four had set a target to increase the proportion of EIBF from 69% to 92% 27. Skin-to-skin contact between mothers and their newborns immediately after delivery facilitates the EIBF within the first hour of delivery 29–35…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations